Givetian ostracods of the Candás Formation (Asturias, North-western Spain): taxonomy, stratigraphy, palaeoecology, relationship to global events and palaeogeographical implications - Maillet, Sebastien; Milhau, Bruno; Vreulx, Michel; Posada, Luis-Carlos Sánchez De (Zootaxa, 2016)
Asturian ostracods of the Givetian carbonate Candás Formation are documented for the first time from the Peran-Perlora and Carranques reference sections. More than 1,200 specimens were extracted from 44 samples by means of the hot acetolysis method. In all, 75 taxa are described herein, of which 21 are formally described and one, Evlanella peranensis Maillet n. sp., is new. All the taxa are marine benthic and belong to the Eifelian Mega-Assemblage. The assemblages recognized are representative of semi-restricted to shallow open-marine palaeoenvironments above the storm wave base. The stratigraphical distribution of the taxa shows a strong faunal renewal in the top of the Candás Formation. Long-ranging taxa found at the base of the formation, of which many are known from the base of the Middle Devonian, disappear within the base of the member C and are replaced above, around the Middle/Upper Givetian boundary, by more cosmopolitan taxa characteristic of the Frasnian. The lower half of the member C is also characterized both by unstable environments and occurrence of some short-ranging opportunistic ostracod taxa. This renewal within shallow water ostracod communities is probably a consequence of the global Taghanic Biocrisis, leading world-widely to extinctions in several faunal groups. Faunal affinities with Givetian ostracod taxa reported in other areas of the world reflect the commonly accepted palaeogeographical patterns. Close relations between the Cantabrian Zone (NW-Spain), the Armorican Massif (W-France), the Mouthoumet Massif (S-France) and North Africa (Morocco and Algeria) suggest a narrow oceanic space between the western European terranes and the northern Gondwanan margin that involves an advanced phase of closure of the Medio-European Ocean.